Determinants of Access to Improved Drinking Water Source and Sanitation Facilities Towards Achieving Sustainable Development Goal-6 in India: Results from National Family Health Survey-5 (2019-2021) - Kumar DS, Sujith; Guthi, Visweswara Rao; Kondagunta, Nagaraj; KR, Subash (National Journal of Community Medicine, 2024)
Background: Sustainable development Goal (SDG) 6 is to “ensure availability and sustainable management of water and sanitation for all”. This study aimed to estimate the proportion of households with access to improved drinking water source and improved sanitation facilities and identify predictors of access to improved drinking water source and improved sanitation facilities. Methodology: We used data from the National Family Health Survey (NFHS-5). Improved sources of drinking water and Improved sanitation facilities were stratified by different socio demographic variables. Multivariate logistic regression was performed to estimate the determinants of Improved sources of drinking water and Improved sanitation facilities. Results: The national level proportion of households’ access to improved drinking water was 93.7% (95%CI 93.6%-93.8%) and access to Improved sanitation facilities was 78.8% (95%CI 78.7%-78.9%). The household related factors which had strong association with greater access to improved drinking water and sanitation facilities were households’ residing in urban areas, wealth index of richest, residing in pucca houses, nuclear families and household with female as Head of the family (Hof). Conclusions: Improvement in access is to be ensured among rural areas, households with poor wealth index and north, central, west and east states for achievement of SDG 6 by 2030.